Perspectives on preventing musculoskeletal injuries in nurses: A qualitative study - Amy Richardson; Gagan Gurung; Sarah Derrett; Helen Harcombe (Wiley, 2019)
Abstract Aims and objectives To explore the perspectives of nursing and physiotherapy academics regarding techniques designed to prevent musculoskeletal pain and injury in nurses. Background High rates of musculoskeletal injuries are evident in nurses, yet there is an absence of research identifying effective interventions to address this problem. Exploring the perspectives of individuals with specialist knowledge in the area could help identify barriers to musculoskeletal injury prevention, and innovative strategies to investigate in future studies. Design Cross‐sectional qualitative descriptive study. Methods Between October-December 2017, group and individual face‐to‐face semi‐structured interviews were used to collect data. All interviews were audio‐recorded. A thematic analysis was performed, with two researchers coding audio files using NVivo software. The Consolidated Criteria for Reporting Qualitative Research Checklist was consulted to ensure complete reporting of all methods and findings. Results Nursing and physiotherapy academics (N = 10) were aware of a range of techniques to prevent musculoskeletal injuries in nurses, including education, equipment, health and safety policy and multi‐disciplinary collaboration. However, several barriers to using these techniques were identified, including age, knowledge and availability of equipment, personal and contextual factors, staffing and time pressures. Several strategies were recommended for further investigation and implementation in clinical practice, such as the sharing of personal experiences, orthopaedic assessments and changes to workplaces that foster a culture of safety. Conclusions Further research is required to reduce musculoskeletal pain and injury among nurses. This research should account for the barriers to current prevention strategies and consider investigating novel interventions. Relevance to clinical practice These findings highlight strategies for preventing musculoskeletal injuries among nurses that are likely to be most effective in clinical practice.